The pandemic of disinformation: fake news in the context of Covid-19 in Brazil - Falcão, Paula (2021)
Since the end of 2019, the world has faced one of the most serious pandemics in history: Covid-19. The risks of contamination, the search for a cure, the need for social isolation, the death numbers that are growing every day. The world had already gone through all this in other health crises, but the current one has particularities: thanks to technological advances and the advent of the internet, today we live in a networked society, in which individuals are globally connected and information circulates intensively through digital devices. With institutions in crisis, authorities lose credibility and we experience the PostTruth Era, where fake news reigns. In this paper, we will discuss this scenario of disinformation, infodemia and disinfodemia and will bring, in an expository way, several fake news disseminated during the pandemic in Brazil - collected in news portals, between March and September 2020, and organized according to the thematic categorization of Posetti and Bontcheva.